Regional Business Cycles in New Zealand: Do they exist? What might drive them? - Viv. B Hall; McDermott C. John (European Regional Science Association (ERSA), 2004)
We use National Bank of New Zealand Regional Economic Activity data, to identify and characterise classical business cycle turning points, for New Zealand's 14 regions and aggregate New Zealand activity. Using Concordance statistic measures, logistic model and GMM estimation methods, meaningful regional business cycles have been identified and a number of significant associations established. All regions exhibit cyclical asymmetry for both durations and amplitudes, and synchronisations between aggregate NZ activity and each region are contemporaneous. The regional cycles rarely die of old age but are terminated by particular events. The regions most highly synchronised with the NZ activity cycle are Auckland, Canterbury, and Nelson-Marlborough; those least so are Gisborne and Southland. Noticeably strong co-movements are evident for certain regions. Geographical proximity matters, and unusually dry conditions can be associated with cyclical downturns in certain regions. There is no discernable evidence of association with net immigration movements, and no significant evidence of regional cycle movements being associated with real house price cycles. The agriculture-based nature of the New Zealand economy is highlighted by the strong influence of external economic shocks on rural economic performance. In particular, there is considerable evidence of certain regional cycles being associated with movements in New Zealand's aggregate terms of trade, real prices of milksolids, real dairy land prices and total rural land prices. JEL Classification: C22, E32, R11, R12, R15 Keywords: Classical business cycle; Turning Points; Regional business cycles; Concordance statistics; New Zealand
Keywords: C22; E32; R11; R12; R15; 330; Classical business cycle; Turning Points; Regional business cycles; Concordance statistics; New Zealand